In Classical Poetry the Turkish Beauty - Nazik, Sıtkı (Türk Dil Kurumu [EN], 2018)
Subjects regarding to beauty of lover in the classical Turkish poetry are generally explained by considering equal with similar things. Imitating of lover by connecting physical or spiritual characteristics belongs to a specific human, community, even being called as a word “Turkish” is occasional case. This word “Turkish”, name of a nation, has meanings such as “strong, elegant, beautiful, lover.” The word “beautiful” among these meanings created through characteristics of Turkish people is used as mostly related with eye in Arabic, Persian and Turkish poetry.In this study, the approach of poets which include the word “Turkish” to describe beauty or condition of lover is examined. In this study that aims to show how related concept is handled in classical poetry, certain divans are examined from the poems of passed of the concept are selected examples are evaluated by commentary method based on meaning. In this study that is expected to contribute to learning of a subject related with classical poem in detail, it is concluded that the meaning assigned to the word “Turkish” or expression “Turkish beauty” by important names who have Turkish poems is shaped mostly within the context of eyes of lover.

Klasik Türk şiirinde sevgilinin güzelliğine dair hususlar, genelde o güzellik unsuruyla benzerlik gösteren varlıklara nispet edilerek anlatılmaktadır. Belirli bir insana, topluluğa ait fiziksel yahut ruhsal niteliklerle bağ kurularak sevgilinin tasvir edilmesi, hatta Türk kelimesiyle anılması az rastlanan bir durumdur. Bir millete isim olan bu kelime “güçlü, zarif, güzel, sevgili” gibi anlamlara gelebilmektedir. Türk insanının özellikleri doğrultusunda kelimeye yüklenen bu anlamlardan “güzel” tabiri, bilhassa gözle irtibatlı olarak Arap, Fars ve Türk şiirinde kullanılmıştır. Bu çalışmada sevgilinin güzelliğini veya durumunu anlatmak için Türk kelimesine yer veren şairlerin bu ifadeye yaklaşımları üzerinde durulmuştur. Klasik şiirde söz konusu kavramın nasıl ele alındığını ortaya koymak maksadıyla yapılan bu çalışmada, belli başlı divanlar taranmış, kavramın geçtiği şiirlerden seçilen örnekler anlama dayalı şerh yöntemiyle değerlendirilmiştir. Klasik şiirle ilgili bir konunun ayrıntılı olarak öğrenilmesine katkı sağlayacağı umulan bu çalışmada, Türkçe şiirleri olan önemli isimlerin “Türk” kelimesi veya “Türk güzeli” ifadesine yükledikleri anlamın, çoğunlukla sevgilinin gözleri bağlamında şekillendiği sonucuna ulaşılmıştır.
KLASIK ŞIIRDE TÜRK GÜZELI